2020
DOI: 10.1186/s12880-020-00497-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BSGI, MRI, mammography, and ultrasound for the diagnosis of breast lesions and their correlations with specific molecular subtypes in Chinese women

Abstract: Background Breast cancer is a leading cause of cancer in females, and is the second leading cancer-related cause of death in this group. Early diagnosis is essential to breast cancer to be effectively treated, and ultrasound, mammography, and magnetic resonance imaging (MRI) represent three key technologies that are utilized for the diagnosis of breast lesions. Breast-specific gamma imaging (BSGI) is an approach to molecular breast imaging that allows for high-resolution radio-imaging that is not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Therapeutic efficacy must therefore be evaluated as quickly and accurately as possible so that appropriate interventional strategies can be formulated while minimizing the risk of toxicity. Breast MRI scans are one of the primary approaches used to gauge patient responses to NAC; however, breast MRI analyses can nonetheless yield high false-positive rates and can overestimate tumor size, whereas BSGI is a more recently developed imaging approach that has been leveraged for both tumor staging and NAC response evaluation [9,13,16]. BSGI is a functional imaging approach that utilizes the positively-charged, fat-soluble 99m Tc-sestamibi radiotracer to estimate mitochondrial metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therapeutic efficacy must therefore be evaluated as quickly and accurately as possible so that appropriate interventional strategies can be formulated while minimizing the risk of toxicity. Breast MRI scans are one of the primary approaches used to gauge patient responses to NAC; however, breast MRI analyses can nonetheless yield high false-positive rates and can overestimate tumor size, whereas BSGI is a more recently developed imaging approach that has been leveraged for both tumor staging and NAC response evaluation [9,13,16]. BSGI is a functional imaging approach that utilizes the positively-charged, fat-soluble 99m Tc-sestamibi radiotracer to estimate mitochondrial metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution bilateral craniocaudal (CC) and mediolateral oblique (MLO) images. Individual image acquisition was conducted for approximately 5 min, with a minimal range of 100 Kcounts/image [9,10]. Two nuclear medicine specialists evaluated BSGI results as per the Society of Nuclear Medicine guidelines [11] for interpreting BSGI results while also considering available baseline ultrasound and mammography images.…”
Section: Bsgimentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies carried out among asymptomatic women, this rate has been reported to be as low as 1.6% to 10.4% [17][18] . However, studies conducted among women with suspected breast lesions/masses have reported a higher malignancy rate ranging from 30% to 69.8% [19][20][21][22][23][24] . Although, some studies conducted among suspected women have reported this incidence to be less than 30%.…”
Section: Discussionmentioning
confidence: 99%